2019
DOI: 10.1177/1464884919885588
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the killing of journalists in the contemporary era: The importance of hybrid regimes and subnational variations

Abstract: Explanations for an increase in the killing of journalists worldwide over the last quarter century include the dangers of war coverage and unsafe conditions in formally democratic countries. Analyzing 1812 killings of journalists from 1992 to 2016, we find that countries with hybrid political regimes mixing liberal and illiberal elements create by far the most dangerous context for journalists, while a particular spatial configuration within those countries, subnational authoritarianism, clarifies the logic of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A cause for concern regarding Bangladeshi journalists, however, is that previous research has suggested that journalists are more unsafe in hybrid regimes like Bangladesh than in a pure autocracy. Hughes and Vorobyeva (2019) found that countries with hybrid regimes are by far the most dangerous environment for journalists as power holders have incentives to violently suppress critical press coverage. They reached this conclusion after analyzing 1812 killings of journalists from 1992 to 2016.…”
Section: Discussionmentioning
confidence: 99%
“…A cause for concern regarding Bangladeshi journalists, however, is that previous research has suggested that journalists are more unsafe in hybrid regimes like Bangladesh than in a pure autocracy. Hughes and Vorobyeva (2019) found that countries with hybrid regimes are by far the most dangerous environment for journalists as power holders have incentives to violently suppress critical press coverage. They reached this conclusion after analyzing 1812 killings of journalists from 1992 to 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, media freedom has declined in almost all parts of the world (Freedom House 2019). Media professionals are increasingly being threatened, harassed, assaulted and killed (Simon 2015;Hughes and Vorobyeva 2019). Most of the attacks remain unresolved which fosters a culture of impunity causing fear and self-censorship among journalists (Waisbord 2002).…”
Section: Context: Legal Struggles For Media Freedom In Ugandamentioning
confidence: 99%
“…However, democratic societies also document threats and attacks from governments, political parties, and corporations (Löfgren Nilsson and Örnebring 2016). Across Latin America, authors have reported that journalists who report on topics pertaining to corruption, human rights, and crime, often experience severe reprisals, including threats and direct attacks from corrupt officials, police, and criminal groups with threats and attacks at times extending towards journalists' families and places of work (Hughes and Vorobyeva 2019;Moskowitz 2020;UNESCO 2014). Investigative journalism in Latin America may yield financial reprisals from advertising sources, including state governors (Podesta 2009;Ramírez and Guerrero 2014).…”
Section: Journalism and Riskmentioning
confidence: 99%
“…While work-related traumas or stressors from reporting are becoming well documented, particularly for those who cover powerful stories on mass violence (see for instance : Anderson 2018;Newman et al 2003), it is also true that journalists who remain within the newsroom can also experience dangerous or stressful events or conditions (Feinstein et al 2014) including forms of workplace violence (Chen et al 2020;Ferreir 2019). These events and conditions are suggested to be linked to greater macro-related structural risks, including changes to the political economy of news that increase labor precarity (Örnebring 2018), cultural and identity-based risks from oppressive normative systems, including from aggressive partisans and extremists (Brambila and Hughes 2019;Waisbord 2020), and risks originating from weak or changing enforcement of the rule of law that increases journalists' vulnerability to corrupt officials, security forces and criminal groups (Gonzalez 2021;Hughes and Vorobyeva 2019).…”
mentioning
confidence: 99%